EFL teacher agency in mediating the socialisation of multilingual learners - Rokita-Jaśkow, Joanna (Glottodidactica, 2023)
English as a Foreign Language (EFL) teachers are seemingly ideally placed to mediate the successful socialisation of multilingual learners into the new school environment for two major reasons. Firstly, as they have effective command of both L1 and L2 and often have experience of living abroad, they tend to exhibit higher levels of openness to new situations, empathy and understanding of the difficulties faced by multilingual learners. Secondly, the English class can itself be a platform for mutual understanding where learners are able to develop both English communication skills and intercultural competence (cf. Hopp, Jakisch, Sturm, Becker & Thoma 2020; Krulatz, Neokleous & Dahl 2022). As English is the language of instruction, it also has the potential to maintain levels of multilingual competence among those learners who already speak English as their heritage language (Banasiak & Olpińska-Szkiełko 2021), e.g. migrant children returning from the UK/Ireland. Drawing on data from a larger project (Rokita-Jaśkow, Wolanin, Król-Gierat & Nosidlak 2022), which consisted of interviewing 23 primary school EFL teachers in various contexts, this paper analyses the possible factors that impact teacher agency in the socialisation of multilinguals. It has been found that teacher agency in that respect appears to stem from teachers’ plurilingual competence and prior teaching experience. Surprisingly, personal experiences of intercultural encounters (e.g. time spent living abroad) or verbalised empathy, had little impact on teacher agency. This finding implies that even language teachers find it difficult to put themselves in the position of the multilingual learner and need specialist training in order to work with multilingual learners, which may convey an important message for educational decision-makers with reference to the formulation of future teacher education guidelines and curricula.